Study on concrete with granite powder replacement with cement, analysis compressive strength - RAJA SHAKYA; Prof. GAUTAM BHADOURIA (International Journal of Multidisciplinary Research and Studies, 2023)
In the world of building, concrete is the material that holds the most weight. A sufficient quantity of synthetic materials, gravel, and water are required in order to produce it. The word "concrete" originates from the Latin word "concrete," which meaning "together it evolves." Cement, first class admixtures, and coarse admixtures are the three primary components that make up concrete. The science of determining relative quantities of concrete elements is known as concrete mix design. The goal of this science is to attain the desired qualities in the most cost-effective manner possible. Concrete is currently the second most important material in use around the globe, and the majority of businesses are looking for ways to produce more cost-effective concrete by switching from using cement to using cementation materials. The building industry makes extensive use of concrete, making it the single most significant material in this sector. As a result of urbanization, the amount of cement that is used in the building sector is continuously increasing.